Images from space - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
M. Adama Seck Cisse, Senegal: 'I would like to offer my contribution to Mailbox on the subject of images from space that aid development, Spore No. 68. The European Meteosat satellite was commissioned towards the end of 1979. It is a geostationary...